Efficient visible light-induced photoelectrocatalytic hydrogen production using CdS sensitized TiO2 nanorods on TiO2 nanotube arrays. Issue 44 (2nd October 2015) - Yu, Jiangdong; Gong, Cheng; Wu, Zhi; Wu, Yongneng; Xiao, Wang; Su, Yufeng; Sun, Lan; Lin, Changjian
Abstract : CdS/TNRs/TNTs were synthesized by combining a hydrothermal method with a sequential-chemical bath deposition method and displayed enhanced visible light-induced photoelectrocatalytic hydrogen production activity compared with TNTs, TNRs/TNTs and CdS/TNTs. Abstract : A novel CdS/TiO2 nanorods/TiO2 nanotube array (CdS/TNRs/TNT) photocatalyst was prepared. The self-organized highly oriented TiO2 nanotube arrays (TNTs) were first synthesized by anodizing Ti sheets. The "flower-like" rutile TiO2 nanorods (TNRs) were then grafted on the TNTs by a hydrothermal method. Subsequently, the CdS quantum dots (CdS QDs) were deposited on the surface of the resulting TNRs/TNTs using a sequential-chemical bath deposition (S-CBD) method. UV-vis diffuse reflectance spectra indicated that the CdS/TNRs/TNTs sample showed significantly enhanced absorption in the range from 350 to 700 nm. The photoelectrocatalytic hydrogen production activities of all samples were evaluated by using Na2 S and Na2 SO3 as sacrificial reagents in water under a 300 W Xe lamp with a UV-light filter ( λ > 420 nm). The results showed that CdS/TNRs/TNTs prepared by hydrothermal reactions for 4 h and S-CBD 15 cycles showed a hydrogen production rate approximately 14 times that of the TNTs. When compared to CdS/TNTs, CdS/TNRs/TNTs showed a 2.3 fold increase in hydrogen production, which can be attributed to the enlarged effective deposition area for CdS QDs by depositing "flower-like" rutile TiO2 nanorods on the TNTs. In addition, CdS/TNRs/TNTs exhibited excellent hydrogen production stability using Na2 S and Na2 SO3 as sacrificial reagents.